2002
DOI: 10.1159/000065966
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Histologic Effects of Daily Topical Application of Creams Containing All-<i>trans</i>-Retinoic Acid or All-<i>trans</i>-Retinoyl β-Glucuronide on Pig Skin

Abstract: The efficacy of all-trans-retinoic acid (tRA) and all-trans-retinoyl β-glucuronide (RAG), a water-soluble metabolite of vitamin A, in the topical treatment of acne is comparable. However, whereas 3.3 mM tRA shows side effects, 3.3 mM RAG does not. To assess the relative toxic and histologic effects (dermal and epidermal changes) of long-term (24-week) daily applications of tRA and RAG on the skin, separate skin patches were measured and marked dorsally on the skin of six 21-day-old, castrated male pigs. Each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Another study found that intravenously administered RAG was not extensively hydrolyzed to RA in SD rats [13]. Two recent studies, one carried out by administering RAG by IP injection in pregnant Sprague-Dawley rats, and the other carried out by topical application on swine skin showed that RAG was much less toxic than RA [14,15]. RAG alone, or in combination with 4-chloro-phenyl acetate were shown to exhibit potent antitumor activity in nude mice injected with LA-N-5 cells obtained from the human neuroblastoma cell line [16].…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that intravenously administered RAG was not extensively hydrolyzed to RA in SD rats [13]. Two recent studies, one carried out by administering RAG by IP injection in pregnant Sprague-Dawley rats, and the other carried out by topical application on swine skin showed that RAG was much less toxic than RA [14,15]. RAG alone, or in combination with 4-chloro-phenyl acetate were shown to exhibit potent antitumor activity in nude mice injected with LA-N-5 cells obtained from the human neuroblastoma cell line [16].…”
Section: Introductionmentioning
confidence: 99%
“…In a 1987 safety assessment of retinyl palmitate and retinol, the Cosmetic Ingredient Review Expert Panel stated that these ingredients are safe as cosmetic ingredients in the present practices of use and concentration. 1 The Panel reviewed newly available studies since that assessment along with updated information regarding types and concentration of use 2 …”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of RA used were the same as those previously reported to induce RA effects. [23][24][25][26][27] To generate RA-treated mice, 0AE1% RA (Sigma Chemical Co., St Louis, MO, U.S.A.) dissolved in DMSO (Sigma) (10 lL cm )2 ) was administered topically to mouse skins dorsally as described previously. 25 The administration of agents was carried out daily for 1 week.…”
Section: Animalsmentioning
confidence: 99%